CONTROLLED WRITING AS ONE OF WRITING EXERCISES - Rindang Widiningrum (Universitas Stikubank (UNISBANK) Semarang, 2013)
There are four skills inlanguage that needed to communicate ideas. Those are speaking, listening,reading and writing. Writing is oneof the skills that the students must learn inclass. This skill seems to be the most difficult for some of the students wholearn English as second or foreign language. At the basic level, writing is anact of committing words or ideas to some medium. On the other hand, writing isa work of inventing ideas, thinking about how to express the ideas andorganizing them into sentences that will be clear to readers. Writing itself is not a skill that cannot belearned. By the help of the teacher and a lot of exercises, the students willbe able to improve their ability in writing. Some exercises that can help thestudents are controlled writing. The examplesof controlled writing are imitating,rewrite a story using the clues given, combining sentences, completingsentences, and arrange sentences into chronological order. The aim of thispaper is to show the need of controlled writing as an exercise to improve students’ability especially beginner in writing for communicating their ideas.Keywords: controlled writing, writing exercises.